PROSESI PERNIKAHAN ADAT DI KELURAHAN CIKORO’ KECAMATAN TOMPOBULU KABUPATEN GOWA - Hajar, St. Hajar; lidiawati, Nur; M, M. Dahlan (Jurnal Adabiyah, 2018)
This study aimed to describe the tradition wedding procession of the Cikoro community and to analyzed the symbolic meaning behind the process. The purpose of this study is achieved by answering the following three issues: 1. How is the wedding procession in the sub-district of Cikoro Tompobulu district Gowa regency? 2. How is the symbolic meaning contained in Wedding Tradition in Kelurahan Cikoro' Tompobulu district of Gowa regency? and 3. How are the Islamic cultural values contained in it?This study found a unique wedding procession and distinct from the wedding procession in general in South Sulawesi. In a community wedding ceremony in the village Cikoro generally consists of several stages of activity. Pre-marital stages, marriage stages, and stages after marriage. The activity is a sequential sequence that should not be mutually exchanged. Key words: Traditional wedding procession, Cikoro, symbolic meaning.   Abstrak Penelitian ini bertujuan untuk mendeskripsikan proses pernikahan adat masyarakat Cikoro’ dan menganalisis makna simbolis di balik proses tersebut. Tujuan penelitian ini tercapai dengan menjawab tiga masalah berikut: 1. Bagaiman prosesi pernikahan di kelurahan Cikoro’ kecamatan Tompobulu kabupaten Gowa? 2. Bagaimana makna simbolik yang terkandung dalam Adat Pernikahan di Kelurahan  Cikoro’ kecamata Tompobulu  kabupaten  Gowa? dan  3. Bagaimana  nilai-nilai budaya  Islam yang terkandung didalamnya?Penelitian ini menemukan adanya prosesi adat pernikahan yang khas dan berbeda dari prosesi pernikahan pada umumnya di Sulawesi Selatan. Dalam upacara pernikahan masyarakat di kelurahan Cikoro’ pada umumnya terdiri atas beberapa tahap kegiatan. Tahapan pra nikah, tahapan nikah, dan tahapan setelah nikah. Kegiatan tersebut merupakan rangkaian yang berurutan yang tidak boleh saling tukar-menukar. Kata kunci: prosesi pernikahan, adat, tahapan nikah